Evaluation of Key Performance Indicators in the Pre-analytical Phase of Testing in a Clinical Chemistry Laboratory of a Reference Institute - Ghauri, Ahsan Ahmad; Munir, Muhammad Usman; Haroon, Zujaja Hina; Younas, Muhammad; Anwar, Muhammad; Kirmani, Sobia Irum (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To check the performance in the pre-analytical phase of testing in the clinical chemistry laboratory of a reference institute using five key performance indicators and to compare these indicators between the morning and night shifts to ascertain the most probable source of pre-analytical errors.Study Design: Comparative cross-sectional studyPlace and Duration of Study: Department of Chemical Pathology & Endocrinology, Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Apr to Sep 2021.Methodology: Defined key performance indicators (KPIs) were observed for a period of six months. The frequency and percentage of each KPI were calculated. Defects per Million were calculated for deriving Six Sigma (σ) values. KPIs were alsocompared between the morning and night shifts.Results: A total of 272,731 samples were observed in which 2306(0.84%) were found haemolysed (σ=3.5), 604 samples (0.22%) were not received in the Department due to various pre-analytic reasons (σ=4.0), 260 samples (0.09 %) were found having insufficient sample volume for analysis (σ=4.5), 181(0.06%) samples were found having improper/ wrong labelling or bar code errors (σ=4.5) and 161(0.05%) samples were delivered in wrong tubes (σ=4.5). KPI-1, KPI-2, and KPI-3 were found to be significantly higher during the night shift than the morning shift.Conclusion: Haemolysed samples and lost-not-received samples were the main causes of pre-analytical errors Key performance indicators aided as an instrument to screen and improve process execution in the laboratory.